Politik Keamanan Jagoan Madura - RADITYA, ARDHIE (Universitas Muhammadiyah Yogyakarta, 2011)
This research explains the local strongmen in Madura, named Blater. The power was not onlyobtained through mastering either economic capital or structural power but through the power can beobtained through managing people security. This research uses descriptive-qualitative method forexplaining the result of this research. The result of this research shows that the democracy has beenused as an opportunity to reach the power conducted by local strongman in Madura. They wereextremely intelligent in creating public fear as a power commodity that was used for political interest,particularly in the election of regional heads. They have established structural-functional relationshipsindirectly between bureaucrats and security apparatus. With courage and respect values, the Blatersuse people’s fears as a bridge to compose security politics in the era of democracy.